Challenges to the implementation of blended learning in Islamic Religious Education Learning in Indonesia - Firmansyah Firmansyah; Ferianto Ferianto; Izet Pehlic (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2024)
This research discusses the definition of blended learning model, classification of blended learning model, benefits of blended learning in Islamic religious education learning, implementation of blended learning model in Islamic religious education learning, and challenges in implementing blended learning model in Islamic religious education learning. This research uses literature review method to analyze the concept of blended learning model implementation in Islamic religious education learning. Data collection was conducted by tracing various literature sources related to blended learning and Islamic religious education learning that included empirical research, theoretical studies, and practice reports from various educational contexts identified through searches in digital academic databases, as well as through cross-referencing of relevant articles. The data analysis used a content analysis approach. The results showed that the implementation of blended learning in Islamic religious education learning offers an innovative and flexible approach to improve the quality and effectiveness of learning. However, the implementation strategy of blended learning must be designed by considering the advantages, disadvantages, and challenges. Such as access to the internet, teacher and learner skills, and digital security. If implemented wisely and adaptively, blended learning in Islamic religious education learning has great potential to enrich learners' learning experience. Therefore, it is important to continuously evaluate and develop, as well as ensure that any challenges are addressed with appropriate and innovative solutions, so that the benefits of blended learning can be felt by all parties involved in Islamic religious education learning.Keywords: blended learning, learning strategies, Islamic religious education learning.